Confirmation and further delineation of the SMG9‐deficiency syndrome, a rare and severe developmental disorder. Issue 11 (7th August 2019) - Lecoquierre, François; Bonnevalle, Antoine; Chadie, Alexandra; Gayet, Claire; Dumant‐Forest, Clémentine; Renaux‐Petel, Mariette; Leca, Jean‐Baptiste; Hazelzet, Tristan; Brasseur‐Daudruy, Marie; Louillet, Ferielle; Muraine, Marc; Coutant, Sophie; et al.
Abstract: Introduction: SMG9 deficiency is an extremely rare autosomal recessive condition originally described in three patients from two families harboring homozygous truncating SMG9 variants in a context of severe syndromic developmental disorder. To our knowledge, no additional patient has been described since this first report. Methods: We performed exome sequencing in a patient exhibiting a syndromic developmental delay and in her unaffected parents and report the phenotypic features. Results: Our patient presented with a syndromic association of severe global developmental delay and diverse malformations, including cleft lip and palate, facial dysmorphic features, brain abnormalities, heart defect, growth retardation, and severe infections. She carried a novel SMG9 homozygous variant NM_019108.3:c.1177C>T, p.(Gln393*), while her unaffected parents were both heterozygous. Conclusions: We confirm that bi‐allelic truncating SMG9 variants cause a severe developmental syndrome including brain and heart malformations associated with facial dysmorphic features, severe growth and developmental delay with or without ophthalmological abnormalities, severe feeding difficulties, and life‐threatening infections.